CORPORATE CAPITAL AND RESTRICTIONS UPON DIVIDENDS. - Ballantine, H. W.; Hills, George S. (The Accounting Review, 1935)
No part of the entire corporate mechanism, a vital instrumentality in modern business, investment and speculation, is more complicated or more poorly designed and comprehended than the legal capital requirements and the attempted safeguards against unsafe distributions of assets to the shareholders such as improper dividends, share purchases and distributions following reductions of legal capital. The article presents a brief survey of the prevailing types of statutory restrictions upon dividends with a view to evaluating the efficiency and ascertaining the shortcomings of the standards prescribed. The concept of the legal or "stated" capital are considered, and different varieties of limitations on cash and share dividends, with comment upon the abuses and defects of the existing systems and the need of some further statutory revision are discussed. Whatever restrictions are adopted as to dividends they should be supplemented by a general requirement of the exercise of reasonable care and prudence not merely to ascertain the existence of book surplus or profits, but also needful liquidity and the financial status generally.